Characterization of large volume subcutaneous injections using computed tomography imaging and simultaneous pressure measurements - Purcell, Mona; Babaee, Sahab; Galluppi, Michael; Cline, John; Hu, Guangli; Petrescu, Ioan; Hughes, Jennifer; Allen, Meredith; Messina, Eric; Persak, Steven; Krishnamachari, Yogita; Lay-Fortenbery, Ashley; et al. (Frontiers in Drug Delivery, 2023)
Many commercially available biologics, previously delivered only intravenously, are being reformulated for subcutaneous delivery to improve patient access and compliance. However, due to inherent solubility limitations, large volume injections (more than 2 ml) are typically required. Different strategies are being explored to improve the tolerability of such injections, including the co-formulation with hyaluronidase and/or implementing different needle designs. While there have been separate reports of measuring injection forces and using imaging to track injection delivery and tissue response, there is no current set of methods to simultaneously characterize the injection delivery (bleb) and measure injection pressures. In this study we describe the development of CT (Computed Tomography) imaging methods in minipigs to characterize the morphology of the bleb following injection, along with inline pressure measurements to assess subcutaneous pressure during injection using two different injection volumes, 4.5 ml and 9 ml. We show that these parameters change with injection volume, and that inclusion of hyaluronidase in the injection increases bleb dispersion and reduces skin distention while also lowering the injection pressure. This method will likely be a valuable tool for assessing and comparing different injection delivery methods and formulations.